Meningkatkan Kreatifitas dan Kerjasama Mahasiswa Dalam Membuat Media Pembelajaran Geografi Menggunakan Model PjBL - Rosanti; Agus Sudiro; Ivan Veriansyah; Eviliyanto (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
This study aims to improve student creativity and collaboration in creating geography learning media, which was previously identified as low. This problem was seen in the 2017 and 2018 classes, where only a handful of students took an active role. To address this problem, Classroom Action Research (CAR) was implemented using the Project-Based Learning (PjBL) model, which adopted Kurt Lewin's design, including the stages of Planning, Action, Observation, and Reflection. The research subjects were 31 students from the Geography Education Study Program at PGRI Pontianak University. The results showed a very significant increase. In Cycle I, the level of student creativity that reached the new standard reached 48.38%, and cooperation was 48.38%. However, after intervention and improvements in Cycle II, there was a drastic increase, with 90.32% of students successfully achieving the established creativity criteria, and 87.09% of students achieving the cooperation criteria. This increase proves that the implementation of the PjBL model is very effective in encouraging essential 21st-century skills, namely creativity and cooperation, in an academic environment.